2011
DOI: 10.4028/www.scientific.net/amr.183-185.225
|View full text |Cite
|
Sign up to set email alerts
|

Research on Cell Model of a Housing Unit

Abstract: Housing unit is studied as cell in this paper. The cell model analyzes structure and usage of each primary apartment and room of a housing unit in a view of a biological cell. Individual human person is abstracted as ATP and electron in this model, and it is demonstrated that human has the dominant impact on urban management and social administration as an electron in a living organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…A previous study indicated that natural dyeing could perform well on the polyester fibers, viz. poly(ethylene terephthalate) (PET), the conventional polyester, and poly(lactic acid) (PLA), the renewable resource-based polyester [3,4]. So, there is a possibility to use natural dyes for dyeing a blend of these synthetic fibers with other fibers which is also natural dyeable.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study indicated that natural dyeing could perform well on the polyester fibers, viz. poly(ethylene terephthalate) (PET), the conventional polyester, and poly(lactic acid) (PLA), the renewable resource-based polyester [3,4]. So, there is a possibility to use natural dyes for dyeing a blend of these synthetic fibers with other fibers which is also natural dyeable.…”
Section: Introductionmentioning
confidence: 99%
“…Basic unit of architecture or housing unit makes up a total building or construction, and they make up to be a neighborhood or social community, then villages and towns forms and finally it comes to somehow big city. [8] What makes city so different from any other ecological system is that human plays a critical and important role in this world, that is, it is a human society. Matters and substances are changed in shape and properties as human needs.…”
mentioning
confidence: 99%